Enhanced Lateral Flow Immunoassay with Double Competition and Two Kinds of Nanoparticles Conjugates for Control of Insecticide Imidacloprid in Honey - Dmitriy V. Sotnikov; Lyubov V. Barshevskaya; Anatoly V. Zherdev; Boris B. Dzantiev (Biosensors, 2023)
Finding optimal conditions for competitive lateral flow immunoassay is a controversial task. The content of specific antibodies labeled by nanoparticles should be simultaneously high to reach intense signals and low to register an influence on the signals for minimal concentrations of the target analyte. We propose to use two kinds of complexes of gold nanoparticles in the assay, with antigen–protein conjugates and with specific antibodies. The first complex interacts both with immobilized antibodies in the test zone and with antibodies on the surface of the second complex. In this assay, the coloration is enhanced by the binding of two-colored preparations in the test zone, whereas the antigen in the sample inhibits both the binding of the first conjugate with the immobilized antibodies and with the second conjugate. This approach is realized for the detection of insecticide imidacloprid (IMD), an important toxic contaminant connected with the recent global death of bees. The proposed technique expands the working range of the assay, that is, in accordance with its theoretical analysis. The reliable change of coloration intensity is achieved for a 2.3-times-lower concentration of the analyte. The limit of IMD detection is 0.13 ng/mL for tested solutions and 1.2 µg/kg for initial honey samples. The combination of two conjugates doubles the coloration in the absence of the analyte. The developed lateral flow immunoassay is applicable for five-fold-diluted honey samples without extraction, does not require additional stages (all reagents are pre-applied to the test strip), and is implemented in 10 min.